Micronutrient intakes among women of reproductive age in Vietnam - Nguyen, Phuong Hong; Nguyen, Hieu; Gonzalez-Casanova, Ines; Copeland, Erika; Strizich, Garrett; Lowe, Alyssa E.; Pham, Hoa; Truong, Truong; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Public Library of Science, 2014)
### Background